Endogenous Growth, Taxes and Government Spending: Theory and Evidence - Denaux, Zulal S. (Valdosta State University, 2005)
This paper provides a theoretical and empirical investigation of the simultaneous effects of taxes and government spending on long-run economic growth in an endogenous growth framework. It is argued that including both taxes and government spending in the model eliminates the omitted variables bias associated with the government budget constraint. A two-sector model is considered: one sector produces physical output and the other produces human capital. Government expenditure is broken into several categories, and several types of taxes are included. One kind of government capital (roads) enters in the physical output sector and another kind (schools) enters in the human capital accumulation sector. In addition, government operating expenditures for schools enters in the human capital accumulation sector. Personal income, corporate income, property, sales and gasoline taxes are included. The property tax is especially interesting because it is a major source of revenue for local government. The theoretical model is estimated using annual panel data of North Carolina counties. This study finds that state-level fiscal policies affect economic growth but county-level fiscal policies do not.
Keywords: Endogenous growth; Taxation; Government spending; Public finance; Expenditures, Public; Government spending policy; Taxation